Eating the afterbirth: An exploration of the myth of motherhood - Power, Pamela Ann. (My University, 2006)
This research report consists of two parts: a theoretical introduction and a creative project. In the theoretical introduction I have examined various pregnancy and child-care manuals together with popular literature in an attempt to explore some of the representations of motherhood. The areas I touched on include: pregnancy, labour pain, natural birth, breastfeeding, postnatal depression, working mothers and child care. The creative project incorporates all these different facets of motherhood and consists of two chapters of a novel written in the popular form referred to as “chick lit”.
Faculty of Humanities School of Language and literature 0005333p PHP@worldonline.co.za
Keywords: Mother; Maternal; Birth; Childcare; Working Mother